2012
DOI: 10.1016/j.actbio.2011.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Remineralization of artificial dentinal caries lesions by biomimetically modified mineral trioxide aggregate

Abstract: Fluoride-releasing restorative materials are available for remineralization of enamel and root caries. However, dentin remineralization is more difficult than enamel remineralization due to the paucity of apatite seed crystallites along the lesion surface for heterogeneous crystal growth. Extracellular matrix proteins play critical roles in controlling apatite nucleation/growth in collagenous tissues. This study examined the remineralization efficacy of mineral trioxide aggregate (MTA) in phosphate-containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
83
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 47 publications
(53 reference statements)
2
83
0
3
Order By: Relevance
“…Polyacrylic acid (PAA) altered the hydroxycarbonate apatite (HCA) induced by BAG 45S5, with smaller structures deposited on the surfaces of enamel WSLs, remineralized using PAA-BAG slurry and assessed using Raman micro-spectroscopy and SEM [7]. The ( COOH) functional group of PAA may bind the calcium and phosphate ions to form nano-precursors small enough to penetrate the carious lesion more effectively [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Polyacrylic acid (PAA) altered the hydroxycarbonate apatite (HCA) induced by BAG 45S5, with smaller structures deposited on the surfaces of enamel WSLs, remineralized using PAA-BAG slurry and assessed using Raman micro-spectroscopy and SEM [7]. The ( COOH) functional group of PAA may bind the calcium and phosphate ions to form nano-precursors small enough to penetrate the carious lesion more effectively [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, comparatively few such studies were conducted on root caries lesions as researchers have generally focused on lesion creation under different conditions [Shellis, 2010;Moron et al, 2013] or the study of fluoride and/or potentially cariostatic agents on de-and remineralization of one particular lesion type in situ [Wefel et al, 1995[Wefel et al, , 2002 and in vitro [Xie et al, 2008;Qia et al, 2012]. Nonetheless, a series of mechanistic studies [Kawasaki et al, 2000;Smith et al, 2005;Preston et al, 2008] found that lesion baseline mineral distribution affects fluoride response under subsequent remineralization, that smaller lesions are more prone to remineralization and that, as shown for enamel [ten Cate and Duijsters, 1982], the mineral and fluoride content of the surface layer determines the rate of remineralization.…”
mentioning
confidence: 99%
“…This strategy reproduced both intrafibrillar and interfibrillar minerals and recapitulated the dimension and order of the apatite crystallites that are found in natural dentin [70][71][72][73]. Using this biomimetic remineralization strategy, both hybrid layers created by etch-and-rinse adhesives [68,74,75] and moderately aggressive self-etch adhesives [65,74,76], as well as 250-to 300-μm-thick completely demineralized dentin lesions, can be remineralized [77][78][79]. This bottom-up remineralization strategy does not rely on seed crystallites, and may be considered as a potentially useful mechanism in extending the longevity of resin-dentin bonds [80] via restoring the dynamic mechanical properties of the denuded collagen within the hybrid layer to approximate those of mineralized dentin [81].…”
Section: Fluoride-free Adhesivesmentioning
confidence: 82%